Más allá de lo étnico: procesos identitarios entre reivindicación y prácticas tradicionales (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This paper presents reflections on ethnic self-consciousness: identity of indigenous peoples, referred to the Pacific and Central-North regions of Nicaragua. The theory that is located in Nicaraguan anthropology is based on the fact that the original populations were almost exterminated by the Spanish conquest, however the elements of identity were reconfigured as is observable from the current manifestations. The exposition in the text refers to the analysis of self-consciousness beyond the surface of modernity, and the denial of the original identity. Anthropology drives to the recognition of the original identity in the current people, manifested in their cultural practices, and social structures. This article analyzes the meaning of ethnic self consciousness in native people, from the seeds of their practice rooted in their collective unconscious. Starting from their ancestral origins, to understand from the logic of identity, the ethnic conscience, linked to current cultural practices. Finally, there are lines of reflection on social and cultural practices, manifested in traditions and customs as ways of preserving the identity of populations.
Keywords: Ethnic self-awareness, ethnicity, native peoples, ancestral origin, cultural identity